Strengthening Qur'anic Education for Students at Rumah Tahfiz Al-Mukhlishun Through a Thematic Tahfiz Approach - Murni, Dewi; Saputra, Indra; Kurniawan, Kurniawan; Hendra, Hendra; Hidayah, Zhiratul (Jurnal Masyarakat Mengabdi, 2025)
This community engagement program aims to improve the quality of Qur'anic education at Rumah Tahfiz Al-Mukhlishun through a thematic tahfiz approach. The main challenge faced by the institution is the students' low contextual understanding of memorized verses and the use of conventional teaching methods. The program involved 10 students participating in 30 intensive training sessions over 10 days. The methodology included training, group mentoring, and structured thematic evaluations focusing on key topics such as monotheism, ethics, social relations, and Islamic law. The results indicated a significant improvement in students' memorization retention and thematic comprehension. Furthermore, this approach increased students' motivation and active engagement in learning. The program demonstrates that the thematic tahfiz approach serves as an innovative solution for making Qur'anic education more meaningful and applicable to daily life